Effect of topical imiquimod as primary treatment for lentigo maligna: the LIMIT‐1 study. (1st May 2017) - Marsden, J.R.; Fox, R.; Boota, N.M.; Cook, M.; Wheatley, K.; Billingham, L.J.; Steven, N.M.; ,; Simpkins, D.; Whitham, D.; Chalmers, J.; Bunker, C.; et al.
Summary: Background: Topical imiquimod is sometimes used for lentigo maligna (LM) in situ melanoma instead of surgery, but frequency of cure is uncertain. Pathological complete regression (pCR) is a logical surrogate marker for cure after imiquimod, although residual LM and atypical melanocytic hyperplasia may not be reliably distinguished. A trial comparing imiquimod vs. surgery might be justified by a high imiquimod pCR rate. Objectives: Primary: to estimate the pCR rate for LM following imiquimod. Secondary: to assess the accuracy of prediction of pCR, using clinical complete regression (cCR) plus negative post‐treatment biopsies, tolerability, resource use, patients' preferences and induced melanoma immunity. Methods: This was a single‐arm phase II trial of 60 imiquimod applications over 12 weeks for LM then radical resection. A pCR rate ≥ 25 out of 33 would reliably discriminate between pCR rates < 60% and ≥ 85%. Clinical response was assessed and biopsies taken after imiquimod. Patients recorded adverse events in diaries. Patient preference was measured after surgery using a standard gamble tool. Results: The pCR rate was 10 of 27 (37%, 95% confidence interval 19–58%). The rate of cCR plus negative biopsies was 12 of 28, of whom seven of 11 had pCR on subsequent surgery. The median dose intensity was 86·7%. Of the 16 surveyed patients, eight preferred primary imiquimod over surgery if the cure rate for imiquimod was 80%, and four of 16 if it was ≤ 40%. Conclusions: The pCR rate was insufficient to justify phase III investigation of imiquimod vs. surgery. Clinical complete response and negative targeted biopsies left uncertainty regarding pathological clearance. Some patients would trade less aggressive treatment of LM against efficacy.